Synergistic Antibacterial Potential and Cell Surface Topology Study of Carbon Nanodots and Tetracycline Against E. coli - Tiwari, Dhermendra K.; Jha, Gargi; Tiwari, Manisha; Kerkar, Savita; Das, Suman; Gobre, Vivekanand V. (Frontiers in Bioengineering and Biotechnology, 2021)
Increasing drugs and antibiotic resistance against pathogenic bacterial creates necessity to explore novel biocompatible material. In this study, we investigated the antibacterial effect of carbon dot (C-dot) against gram-negative E. coli bacteria and suggested effective synergistic dose of tetracycline with C-dot by using mathematical modeling of antibacterial data. Colony count and growth curve study clearly showed enhanced antibacterial activity against E. coli when synergistically treated with C-dot + tetracycline even at 10 times lower concentration than minimum inhibitory concentration (MIC). Richards model-fit of growth curve clearly showed increase in doubling time, reduction in growth rate and early stationary phase in synergistic treatment with 42% reduction in growth rate (μm) compare to control. Morphological study of E. coli synergistically treated with C-dot + tetracycline showed cell damage and binding of C-dot with bacterial cell membrane in scanning electron microscopy. We further validated topological changes, cell surface roughness and significant change in height profile (ΔZ) among the control and treated E. coli cells viewed under atomic force microscopy, In the current study we confirmed the effective antibacterial doses of both C-dots and tetracycline, which is much lower than the MIC concentration.